An observational cross-sectional investigation of foodservice management and general management practices in schools running the National School Nutrition Programme (NSNP) in the formal and informal urban areas of Pietermaritzburg, KwaZulu-Natal, South Africa - Meaker, Jill (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr (Human Nutrition))--Stellenbosch University, 2008.